Therapy of chronic myeloid leukemia with imatinib mesylate in Brazil: a study of 98 cases - Funke,Vaneuza A. M. (2005)
Chronic Myeloid Leukemia (CML) is a clonal disease characterized by balanced translocation between chromosomes 9 and 22 (Philadelphia chromosome). The resulting BCR-ABL gene has tyrosine kinase activity which stimulates cellular growth. Imatinib mesylate is a potent and specific inhibitor of all ABL related kinases. Ninety-eight CML patients were treated with imatinib mesylate from October 2000 to January 2003. Disease stage was: late chronic phase resistant or intolerant to alpha-interferon (CP): 28; accelerated phase (AP): 55; blastic phase (BP): 15 patients. Dose: 400 mg for CP and 600 mg for AP or CB. The objectives were to evaluation the efficacy, safety and survival with imatinib mesylate therapy in all phases of CML. The median follow up time was 545 days (range: 7-862), complete hematologic response was 86% in CP, 47% in AP and 13% in BP. Complete cytogenetic response was 61%, 24% and 0% respectively. BCR-ABL was not detected by nested RT-PCR in 9% of patients. Grade 3-4 hematologic toxicity was seen in 21% of CP, 74% of AP and 87% of BP patients. Grade 3-4 non-hematologic toxicity was observed in 11% of CP, 51% of AP and 53% of BP patients. Two-year overall survival was 64% for all patients, 96% for CP and 36% for AP patients. All BP patients died within a median of 60 days. Imatinib mesylate induced cytogenetic responses in Brazilian patients with previously treated CML in chronic and accelerated phase. Adverse events are similar to those reported in the literature, except for lower rates of gastrointestinal symptoms and muscle cramps in our study group.